2015
DOI: 10.4103/0366-6999.152458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Dual Antiplatelet Therapy Use in Patients Following Everolimus-eluting Stent Implantation

Abstract: Background:Studies have suggested that use of prolonged dual antiplatelet therapy (DAPT) following new generation drug-eluting stent implantation may increase costs and potential bleeding events. This study aimed to investigate the association of DAPT status with clinical safety in patients undergoing everolimus-eluting stent (EES) implantation in the SEEDS study (A Registry to Evaluate Safety and Effectiveness of Everolimus Drug-eluting Stent for Coronary Revascularization) at 2-year follow-up.Methods:The SEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Another randomized study about DAPT duration for EES, ITALIC trial, showed rates of bleeding and thrombotic events were not significantly different according to 6-versus 24-month DAPT after PCI in good aspirin responders [17]. The registry study of EES, SEED registry, also concluded that DAPT duration was not an independent risk factor for the composite endpoint including all-cause death, all MI, stroke, definite/probable stent thrombosis, and major bleeding [23]. A much shorter term of DAPT could be acceptable for 2nd generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized study about DAPT duration for EES, ITALIC trial, showed rates of bleeding and thrombotic events were not significantly different according to 6-versus 24-month DAPT after PCI in good aspirin responders [17]. The registry study of EES, SEED registry, also concluded that DAPT duration was not an independent risk factor for the composite endpoint including all-cause death, all MI, stroke, definite/probable stent thrombosis, and major bleeding [23]. A much shorter term of DAPT could be acceptable for 2nd generation DES.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] In this issue of Chinese Medical Journal , Zhang et al . [ 14 ] investigated the relationship between DAPT use and clinical safety in Chinese patients undergoing everolimus-eluting stent implantation (the SEEDS study). The major strength of this elegant study was that it included a large cohort of high-risk patients with small vessel disease, long lesions, or multi-vessel disease and assessed outcomes during long-term follow-up.…”
mentioning
confidence: 99%